Privatisasi BUMN dan Reorientasi Peran Negara di Sektor Bisnis Pasca Orde Baru (Jurnal Strategi dan Bisnis, 2014)
This research describes dynamic of inter actors relation during process of privatization of Indonesia’s state owned enterprises in the post New Order era. Privatization means govenment policy aimed at enabling private sector to take over state owned enterprises. Privatizations can also be defined as a set of stage taken to minimize the role of government in order to step up the role of private sector in economics and assets ownership. Privatization as an economical policy doesn’t exist in “empty room”. Privatization policy must be viewed a product of political process. So, the success or failure of this policy is highly influenced by political context. In case of Indonesia, privatization policy did’nt succeed to achieve the goals because of many political constrain happened during the implementation. Keyword: privatization, state owned enterprises, politics